The association between adverse childhood experiences and peripartal pain experience - Zehetmeier, Katharina Fiona; Fröhlich, Melissa Kathrin; Schilder, Andreas; Lis, Stefanie; Schmahl, Christian; Treede, Rolf-Detlef; Sütterlin, Marc (Pain, 2023)
Adverse childhood experiences (ACEs) are associated with altered ongoing and evoked pain experiences, which have scarcely been studied for the peripartum period. We aimed to investigate how ACEs affect pain experience in pregnancy and labor. For this noninterventional trial with a short-term follow-up, pregnant women were divided into a trauma group (TG) with ACEs (n = 84) and a control group (CG) without ACEs (n = 107) according to the Childhood Trauma Questionnaire. Pain experience in pregnancy and labor was recorded by self-report and the German Pain Perception Scale. Pain sensitivity prepartum and postpartum was assessed by Quantitative Sensory Testing and a paradigm of conditioned pain modulation (CPM), using pressure pain thresholds (PPTs) and a cold pressor test. The TG showed higher affective and sensory scores for back pain and a more than doubled prevalence of preexisting back pain. Pelvic pain differences were nonsignificant. The TG also exhibited increased affective scores (1.71 ± 0.15 vs 1.33 ± 0.11), but not sensory scores for labor pain during spontaneous delivery. There were no group differences in prepartum pain sensitivity. While PPTs increased through delivery in the CG (clinical CPM), and this PPT change was positively correlated with the experimental CPM (r = 0.55), this was not the case in the TG. The association of ACEs with increased peripartal pain affect and heightened risk for preexisting back pain suggest that such women deserve special care. The dissociation of impaired clinical CPM in women with ACEs and normal prepartum experimental CPM implies at least partly different mechanisms of these 2 manifestations of endogenous pain controls.